A qualitative study of conflict experiences of Chinese physicians and nurses experiencing death of relatives: effects of dual roles - Xin, SiYing; Liang, GuanMian; Miao, QunFang; Lyu, Wei; Fan, SiYao; Ning, HanYi; Zhang, JingXuan (Frontiers in Psychiatry, 2025)
IntroductionThis study explored experiences of conflict among Chinese Physicians and Nurses following the loss of a loved one. This study aimed to examine the mechanisms behind these conflicting experiences as perceived by Chinese Physicians and Nurses.MethodsThis qualitative exploratory study was conducted in three Chinese hospitals. Semi-structured in-depth interviews were conducted with 16 Physicians and Nurses members using a descriptive phenomenological analysis. Colaizzi’s seven-step analysis was used to analyze the interview data.ResultsThe following three themes and six sub-themes were identified: terminal stage (the responsibility exacerbates the burden of medical decision-making and professional expertise exacerbating internal conflict); acute loss stage (the experience of bereavement disrupts the professional values of medical personnel and emotional projection and avoidance of similar operations); bereavement recovery (reflection on the meaning of the profession and reconceptualization of death).ConclusionThese dual roles place significant psychological pressure on the Chinese Physicians and Nurses and lead to emotional fluctuations and complex internal conflicts when facing the death of their loved ones. Hospital administrators should recognize these contradictions, understand their complex emotions, and provide appropriate social support to address the needs of the Physicians and Nurses.